(Design) thinking out loud: adolescents' design talk in a library makerspace tabletop game design camp. Issue 9 (10th August 2021) - Kessner, Taylor M.; Parekh, Priyanka; Aguliera, Earl; Pérez Cortés, Luis E.; Tran, Kelly M.; Siyahhan, Sinem; Gee, Elisabeth R.
Abstract : Purpose: This paper aims to explore how making tabletop board games elicited adolescents' design thinking during their participation in a summer game design camp at their local library. Design/methodology/approach: This study leverages qualitative approaches to coding transcripts of participants' talk. This study uses the design thinking framework from the Hasso-Plattner Institute of Design at Stanford University as provisional codes to identify and make sense of participants' verbalized design activity. Findings: This study found that the making context of designing tabletop board games elicited a high frequency of design talk in participants, evidenced by both quantitative and qualitative reports of the data. Additionally, participants in large measure obviated constraints on their design activity imposed by linear conceptions of the design thinking model this study introduces, instead of moving fluidly across design modes. Finally, participants' prior experiences in both life and in regard to games significantly influenced their design study. Originality/value: This study highlights the unique affordances of making-centric approaches to designing tabletop games in particular, such as participants' quick and sustained engagement in the study of design. This study also highlights the need for conceptions of design thinking specific to designing games.